2021
DOI: 10.3390/w13233399
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Urban Water Security in the Indus Basin, Pakistan—Priority Actions for Karachi and Lahore

Abstract: Despite growing recognition of solutions to water scarcity challenges, decision-makers across the world continue to face barriers to effective implementation of water planning, governance and management. This is evident in the cases of Lahore and Karachi in the Indus Basin in Pakistan and illustrated through the experiences of the provincial government departments and utilities. Water scarcity and associated challenges are continuing to impose significant costs on these cities, which continue to grow as water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Leakages, ineffective management, and lack of future planning are all serious obstacles faced by water sanitation services in Karachi. Numerous household and drinking water pipelines run parallel to sewage discharge pipelines and occasional leakages are caused by lack of regular cleaning, especially post monsoon season [ 10 ]. This has led to the bacterial contamination of an already scarce water supply, indicating poor management and incompetency of local authorities [ 10 ].…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leakages, ineffective management, and lack of future planning are all serious obstacles faced by water sanitation services in Karachi. Numerous household and drinking water pipelines run parallel to sewage discharge pipelines and occasional leakages are caused by lack of regular cleaning, especially post monsoon season [ 10 ]. This has led to the bacterial contamination of an already scarce water supply, indicating poor management and incompetency of local authorities [ 10 ].…”
Section: Challengesmentioning
confidence: 99%
“…In addition to chemical contaminants, high levels of Escherichia coli (E.coli) were found in Karachi's water sources and the city's water was labelled as the most contaminated water in all of Sindh by Pakistan Council of Research in Water Resources' (PCRWR) research teams [ 12 ]. This excessive contamination of groundwater means it requires treatment before it is safe for consumption and yet only 62% households receive water with any prior treatment while 1.91 of the 2.16 million cubic meters (mcm) of wastewater remains untreated on a daily basis [ 10 ]. Furthermore, many residents have complained that the water tastes salty or looks cloudy and have often found insects crawling in it.…”
Section: Challengesmentioning
confidence: 99%
“…The lack of funding can lead to inadequate sanitation infrastructure, such as lack of proper toilets and waste management systems, which can lead to health and environmental problems. The literature has also suggested that the government and international organizations have been working to address this issue by providing funding and assistance for sanitation projects, but more funding is needed to fully address the problem (Syvrud, et al, 2021). Additionally, the lack of proper sanitation facilities disproportionately affects the poor, women and children.…”
Section: Theme 6-limited Fundingmentioning
confidence: 99%
“…Each year, as summer approaches, the city starts facing conditions of acute scarcity [27]. With increased heat spells, there is an increased urban demand for water [28]. Studies of temporal dynamics of access and quality of water in urban slums of India [29], and water demand datasets from several cities across the globe [30], demonstrate that the consumption for water is highly dynamic across multiple timescales (sub-daily to seasonal changes).…”
Section: Introductionmentioning
confidence: 99%